2017
DOI: 10.1002/cmdc.201700387
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Synthetic Human MUC1 Glycopeptide Vaccine against Tumor‐Associated MUC1 Breaks Tolerance in Human MUC1 Transgenic Mice

Abstract: Breaking tolerance is crucial for effective tumor immunotherapy. We showed that vaccines containing tumor-associated human MUC1 glycopeptides induce strong humoral antitumor responses in mice. The question remained whether such vaccines work in humans, in systems where huMUC1 is a self-antigen. To clarify the question, mice transgenic in expressing huMUC1, mimicking the self-tolerant environment, and wild-type mice were vaccinated with a synthetic vaccine. This vaccine comprised STn and Tn antigens bound to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…51 The MUC1 immune tolerance in MUC1.Tg mice leads to great difficulties in eliciting effective antibody responses against the protective MUC1 epitopes. 5254 With our first generation vaccine construct Q β -MUC1 5–8, we observed significantly weaker binding of MUC1 expressing tumor cells by postimmune sera from Tg mice compared to those from WT mice despite similar levels of total antibodies elicited against the immunizing MUC1 structures 1–4. Similar phenomena of low tumor cell binding were observed in clinical studies of MUC1 based vaccines in human patients.…”
Section: Discussionmentioning
confidence: 86%
“…51 The MUC1 immune tolerance in MUC1.Tg mice leads to great difficulties in eliciting effective antibody responses against the protective MUC1 epitopes. 5254 With our first generation vaccine construct Q β -MUC1 5–8, we observed significantly weaker binding of MUC1 expressing tumor cells by postimmune sera from Tg mice compared to those from WT mice despite similar levels of total antibodies elicited against the immunizing MUC1 structures 1–4. Similar phenomena of low tumor cell binding were observed in clinical studies of MUC1 based vaccines in human patients.…”
Section: Discussionmentioning
confidence: 86%
“…Investigators in the Kunz laboratory have chemically synthesized a wide range of glycopeptides based on the TR of MUC1 and have evaluated various formulations of these (containing factors to recruit innate immunity and/or CD4 help) for antibody induction in WT mice [ 35 , 36 ]. Some of these new antibodies show specificity for the tumour MUC1 glycoforms [ 37 ] and humoral and cellular immune responses to one vaccine formulation (1TR carrying Tn and STn bound to tetanus toxin) have been detected in MUC1 transgenic mice where human MUC1 is expressed from the MUC1 promoter [ 38 ].…”
Section: Preclinical Studies and Combination Therapiesmentioning
confidence: 99%
“…When presented by DCs in MUC1 transgenic mice, MUC- reactive CD4 T-cell responses have been documented [ 28 , 50 ], along with the induction of humoral immunity [ 28 , 50 ] . Moreover, several investigators have demonstrated that MUC1 vaccines carrying the Tn and/or STn glycan are not subject to self-tolerance in MUC1 transgenic mice [ 38 , 46 , 51 ].…”
Section: Applying Research Findings To Immunotherapeutic Strategiesmentioning
confidence: 99%
“…The unlinked adjuvant/ antigen delivery may lead to activation of DC that have not been loaded with antigen and loading with antigen of DC that have not been activated by adjuvant. Therefore a methodology that leads to efficient antigen loading and DC activation of the same DC, includes a conjugation of antigen and adjuvant (Abdel-Aal et al, 2014;Liu et al, 2015;Stergiou et al, 2017;Zom et al, 2016) for efficient uptake and activation. Targeted delivery via DEC2015 (Birkholz et al, 2010) also displays improved antigen uptake by DCs through the mannose receptor (Morse et al, 2011), and other strategies exists and can target delivery to a given cell type (Tacken et al, 2007).…”
Section: Introductionmentioning
confidence: 99%